+0  
 
+1
216
3
avatar

3e^x + 12x = 0

Guest Mar 22, 2017
Sort: 

3+0 Answers

 #1
avatar+442 
+2

3 ex + 12x = 0         | - 12x

3 ex = -12x              | ÷ 3

ex = -4x                   | ÷ -4

-(ex/4) = x

x = -(ex/4)

MWizard2k04  Mar 22, 2017
 #2
avatar+26250 
+2

You need a graphical or numerical method to find the value of x here.

 

It's a good idea to draw a graph anyway to get a good initial estimate for an iterative numerical method:

 

 

So x ≈ -0.204

.

Alan  Mar 22, 2017
edited by Alan  Mar 22, 2017
 #3
avatar+442 
0

Thanks for the suggestion.

MWizard2k04  Mar 22, 2017

6 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details